Design and Synthesis of Iron‐Doped Nanostructured TiO2 and Its Potential Use in the Photodegration of Hazardous Materials Present in Personal Care Products. Issue 18 (22nd June 2017) - Bonfrate, Valentina; Manno, Daniela; Buccolieri, Alessandro; Padmanabhan, Sanosh K.; Licciulli, Antonio; Serra, Antonio; Braione, Eugenia; Calcagnile, Lucio; Giancane, Gabriele
Abstract: Parabens and phenoxyethanol are chemical compounds widely used as preservatives and antimicrobial agents in cosmetic and personal care products. The issue of their effect on human and environmental health is a particularly topical and relevant one that many national and international agencies reported about the risk from the use of such compounds. In the present paper, iron doped TiO2 nanoparticles were synthetized and characterized by morphological and spectroscopic techniques. The proposed synthesis was designed to improve the photocatalytic activity of the nanostructures towards the two preservatives compounds when irradiated by a visible light, in order to optimize the effect of natural irradiation on the photodegradation of the two compounds. Preliminary photocatalytic tests showed that the analytes' concentration in water solutions under illumination in presence of both iron‐doped TiO2 and pure TiO2 decreased. A sensible enhancement of photocatalysis of both propylparaben and phenoxyethanol was recorded in presence of the Fe‐doped nanostructures as a consequence of the physical and chemical properties of the catalyst. Abstract : TiO2 nanoparticles were doped with iron atoms and it was demonstrated that their photocatalytic activity under visible light irradiation towards phenoxyethanol (PHXETOH) and a commercial paraben derivative (E216) was strongly enhanced. PHXETOH and E216 are largely used in the personal care products and their dangerous effects on the human and environmental health are known, so the possibility to photodegraded them under solar irradiation is very appealing. Kinetic studies about the effect of the doped nanoparticles on the preservative compounds clearly demonstrated an efficient photodegradation of the compounds under visible light